2014
DOI: 10.1590/1414-431x20142910
|View full text |Cite
|
Sign up to set email alerts
|

Putative role of ischemic postconditioning in a rat model of limb ischemia and reperfusion: involvement of hypoxia-inducible factor-1α expression

Abstract: Hypoxia-inducible factor-1α (HIF-1α) is one of the most potent angiogenic growth factors. It improves angiogenesis and tissue perfusion in ischemic skeletal muscle. In the present study, we tested the hypothesis that ischemic postconditioning is effective for salvaging ischemic skeletal muscle resulting from limb ischemia-reperfusion injury, and that the mechanism involves expression of HIF-1α. Wistar rats were randomly divided into three groups (n=36 each): sham-operated (group S), hindlimb ischemia-reperfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…As reported in these studies, the post-con had positive impact on muscle wet content, 19,20,27,29,33 cellular redox state, 20,26,27,33 local inflammation, [18][19][20][28][29][30] contractility, 19 mitochondrial function, 18,26 muscular gene expression patterns, 20,26,28,30 as well as on histological muscle damage. [18][19][20][28][29][30]33 Two studies 18,33 showed that mechanical post-con reduced MPO, which is a marker of systemic inflammatory response. However, no statistical difference in MPO between the mechanical post-con and control groups was revealed in another study.…”
Section: Outcomes Of Mechanical Postconditioning In Muscle Flapsupporting
confidence: 58%
See 1 more Smart Citation
“…As reported in these studies, the post-con had positive impact on muscle wet content, 19,20,27,29,33 cellular redox state, 20,26,27,33 local inflammation, [18][19][20][28][29][30] contractility, 19 mitochondrial function, 18,26 muscular gene expression patterns, 20,26,28,30 as well as on histological muscle damage. [18][19][20][28][29][30]33 Two studies 18,33 showed that mechanical post-con reduced MPO, which is a marker of systemic inflammatory response. However, no statistical difference in MPO between the mechanical post-con and control groups was revealed in another study.…”
Section: Outcomes Of Mechanical Postconditioning In Muscle Flapsupporting
confidence: 58%
“…Based on the results of the published articles (►Tables 1-4), rats and mice 9,10,17,[19][20][21][23][24][25][26][27][28][29][30][31][32] are the common animal models used for the study of post-con. There are also several other animal models undertaken as flap models, which were not widely used in experimental studies, including pigs 18 and rabbits.…”
Section: Resultsmentioning
confidence: 99%
“…The production of a number of metabolites such as beta endorphins, prostaglandins and hypoxia-inducible factor-1 α (HIF 1 α) are postulated to result from ischemia induced by full or partial restriction of the brachial artery during IHG exercises (Stiller-Moldovan et al, 2012; Wong and Wright, 2014; Wong et al, 2015). These metabolites play a number of roles including, supporting the immune system, managing inflammation (Cabot et al, 1997; Pedersen and Hoffman-Goetz, 2000), vasodilation and vasoconstriction (Davidge, 2001), stimulating angiogenesis, and tissue repair and regeneration (Wang et al, 2014). It may be that the intensity of the hand grip contraction employed during IHG exercise determines the existence or absence of reactive hyperemia; intuitively, even at intensities less than 55% of MVC partial occlusion of blood flow is likely.…”
Section: Isometric Exercise Trainingmentioning
confidence: 99%
“…Also, controlling bleeding due to accidents occurring in distant places and treatments for joint diseases or contractures requires a tourniquet. The use of the tourniquet entails reversible injury triggered by ischemic conditions during determined periods of time [1][2][3]. Arthroscopic procedures, for instance, are performed during 15 to 60 minutes, while to transport an injured person from far places to the nearest health institution, can require two to three hours.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the last 20 years, the evidence has pointed out that ischemic conditions less than three hours caused by an acute compartmental syndrome, tourniquet or artery clamp, for example, lead to necrosis [3,13]. The stem cells of the skeletal striated muscle tissue, called satellite cells, are postnatal myogenic precursors that can regenerate the myocytes [14].…”
Section: Introductionmentioning
confidence: 99%